Comparative histological study of gametogenesis in diploid and triploid pacific oysters (Crassostrea gigas) reared in an estuarine farming site in France during the 2003 heatwave - Normand, Julien; Le Pennec, Marcel; Boudry, Pierre (Aquaculture, 2008)
We compared the temporal dynamics of gametogenesis in diploid and triploid Pacific oysters (Crassostrea gigas) using histology. Oysters were reared in an estuarine farming site in Brittany over 3 years and their gametogenesis was monitored over the exceptionally hot summer of 2003. Both diploids and triploids showed active gametogenesis, but a high proportion of triploids remained at early stages of gonad development. Gametogenesis of triploids was characterized by the simultaneous occurrence of gonias and immature cytes together with mature gametes rather than overall retardation, though some triploids showed complete gonad maturation. Evidence of spawning was seen in both groups, and the quantity of germinal products emitted appeared to be similar in triploids and diploids, though triploids were much heavier than diploids. Our study supports previously reported experimental observations and suggests that gonad development in triploid Pacific oysters can be enhanced when these oysters are reared in the field under unusually warm conditions.